Distributional Effects of Competition: A Simulation Approach - Carlos Rodriguez Castelan; Abdelkrim Araar; Eduardo A. Malásquez; Sergio Olivieri; Tara Vishwanath (Institute of Labor Economics (IZA), 2021)
Understanding the economic and social effects of the recent global trends of rising market concentration and market power has become a policy priority. To fill this knowledge gap, this paper introduces a simple simulation method, the Welfare and Competition tool (WELCOM), to estimate with minimum data requirements the direct distributional effects of market concentration through the price channel. Using this simple yet novel tool, this paper illustrates the likely distributional effects of reducing concentration in two markets in Mexico that are known for their high level of concentration: mobile telecommunications and corn products. The results show that increasing competition from four to 12 firms in the mobile telecommunications industry and reducing the market share of the oligopoly in corn products would achieve a combined reduction of 0.8 percentage points in the poverty headcount as well as a decline of 0.32 points in the Gini coefficient.
Keywords: C15; D31; D42; D43; E37; 330; poverty; inequality; market concentration; distributional effects; simulation; Mexico